Field notes contributed by Joseph P. Schaufenbuel, fall 1982 - Schaufenbuel, Joseph P.et al (1982)
Field notes were contributed by Joseph P. Schaufenbuel.This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of fall 1982. Epson - sheet feed